Motor Deficits after Cerebellar Tumor Resection - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Cognitive and motor performance after resection of a cerebellar tumor was studied in 22 patients (age range 10-28 years) at University of Minnesota, MN.